Influence of Elicitation and Germination Conditions on Biological Activity of Wheat Sprouts - Dariusz Dziki; Urszula Gawlik-Dziki; Monika Kordowska-Wiater; Monika Domań-Pytka (Journal of Chemistry)
The influence of elicitation, time, and temperature of germination on the biological activity of wheat sprouts was studied. The total phenolics content (TPC), antioxidant activity (AA), and microbiological purity of seeds of three wheat cultivars elicited with Saccharomyces cerevisiae (Y) and Salix daphnoides bark extracts (W) and their mixture (1 : 1) germinated in different conditions were studied. The increase of germination time caused an increase the TPC and AA for all tested wheat cultivars. Germination temperature also influenced these parameters. Generally the highest values in TPC were obtained for sprouts germinated at 20°C. This tendency was found for all tested wheat cultivars. The highest values of TPC and AA were obtained after elicitation by S. daphnoides bark extract. The results of microbiological examination showed that generally for seeds germinated at lower temperature (15°C and 20°C) and during 2 and 4 days the molds were not detected and the levels of aerobic bacteria did not exceed the usually accepted limits. Taking into account both biological activity and microbiological purity of samples the best quality sprouts were in the most cases obtained for wheat germinated during four days at 20°C and elicited by W.